Inter Observer Agreement in Evaluating the Position, Shape and Appearance of Mental Foramen by Panoramic Radiography - Shahrazad Sami (University of Mosul, College of Dentistry, 2010)
Aims : the study aims is to examine the inter- observer variability in radiographic interpretation of the variable position , shape and appearance of mental foramen. Materials and Methods: Four examiners, two dental radiologists and two oral surgeons evaluated 30 panoramic radiographs to evaluated the position, shape and appearance of mental foramen. Results: The most frequent position of mental fo-ramen was between first and second premolars then followed by those below the apices of the first and second premolars and the most frequent shape of mental foramen was irregular where separated type is the frequent appearance of mental foramen. For agreement there was no significant difference between two radiologist for position ,shape and appearance of mental foramen , but with a significant difference was found between four observer, for the position of mental foramen. Conclusions: The study concluded that the position of mental foramen is most commonly below and between the pre-molar teeth and the most frequent shape are irregular and appearance separated type